Generation of sphingosine-1-phosphate is enhanced in biliary tract cancer patients and is associated with lymphatic metastasis - Yuki Hirose (Nature Portfolio, 2018)
Abstract Lymphatic metastasis is known to contribute to worse prognosis of biliary tract cancer (BTC). Recently, sphingosine-1-phosphate (S1P), a bioactive lipid mediator generated by sphingosine kinase 1 (SPHK1), has been shown to play an important role in lymphangiogenesis and lymph node metastasis in several types of cancer. However, the role of the lipid mediator in BTC has never been examined. Here we found that S1P is elevated in BTC with the activation of ceramide-synthetic pathways, suggesting that BTC utilizes SPHK1 to promote lymphatic metastasis. We found that S1P, sphingosine and ceramide precursors such as monohexosyl-ceramide and sphingomyelin, but not ceramide, were significantly increased in BTC compared to normal biliary tract tissue using LC-ESI-MS/MS. Utilizing The Cancer Genome Atlas cohort, we demonstrated that S1P in BTC is generated via de novo pathway and exported via ABCC1. Further, we found that SPHK1 expression positively correlated with factors related to lymphatic metastasis in BTC. Finally, immunohistochemical examination revealed that gallbladder cancer with lymph node metastasis had significantly higher expression of phospho-SPHK1 than that without. Taken together, our data suggest that S1P generated in BTC contributes to lymphatic metastasis.